2016
DOI: 10.1016/j.matdes.2016.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the medium velocity impact response of sandwich panels with different cores

Abstract: The impact response of sandwich panels is not only dependent on the facesheet but also on the core material. This paper compares the dynamic response of sandwich panels with different core materials when subjected to medium velocity impacts. The sandwich panels were made of aluminium facesheets with five different cores, viz., low density balsa wood, high density balsa wood, cork, polypropylene honeycomb, and polystyrene foam. All the specimens were impacted by an instrumented projectile with a hemispherical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 33 publications
0
46
0
1
Order By: Relevance
“…Faces are generally made of metal alloys [1], fiber reinforced composites [2] or fiber metal laminates [3] and are responsible for carrying the transverse loads or bending moments. The core of sandwich structures comprises of honeycombs [4], corrugated materials [5], polymeric/metallic foams [6,7], lattices [8] or balsa wood [9] and is responsible for absorbing the impact energy by local plastic deformation whilst still offering enough overall support to prevent high local bending strains in the facesheets. A comprehensive review of the current trends in the research and applications of sandwich structures is done by Birman and Kardomateas, [10].…”
Section: Introductionmentioning
confidence: 99%
“…Faces are generally made of metal alloys [1], fiber reinforced composites [2] or fiber metal laminates [3] and are responsible for carrying the transverse loads or bending moments. The core of sandwich structures comprises of honeycombs [4], corrugated materials [5], polymeric/metallic foams [6,7], lattices [8] or balsa wood [9] and is responsible for absorbing the impact energy by local plastic deformation whilst still offering enough overall support to prevent high local bending strains in the facesheets. A comprehensive review of the current trends in the research and applications of sandwich structures is done by Birman and Kardomateas, [10].…”
Section: Introductionmentioning
confidence: 99%
“…They found that plates with non-orthogonal layout had better loading performance. Cheng et al [4] investigated the behavior of sandwich composite plates with aluminum foam core under quasi-static in uence and observed the behavior of samples in three stages of elastic, yield and failure. As the epoxy resin layer increased, the amount of energy absorbed increased.…”
Section: Introductionmentioning
confidence: 99%
“…The most common wood studied in sandwich composites under impact is balsa but it is mostly investigated from an experimental point of view or for comparison purposes, for example [27][28][29]. However, several authors have focused more precisely on the modeling of the crushing of wood.…”
Section: Introductionmentioning
confidence: 99%